Coaches' perceptions and practices regarding set pieces in football: A survey study of Bulgarian and international coaches - Ivanov, Danail (Tanjungpura Journal of Coaching Research, 2026)
Background. Set pieces represent a significant component of modern football performance, yet their systematic preparation remains inconsistent across coaching levels. Objectives. This study aimed to examine coaches’ perceptions and practices regarding set-piece training among Bulgarian and international football coaches. Methods. This study investigated the perceptions and training practices related to set pieces among 342 Bulgarian football coaches and 49 international coaches (N = 391), using an online descriptive survey with Likert-scale, categorical, and open-ended items. Data were analyzed via descriptive statistics, chi-square tests of independence, Cramér's V, and Spearman rank correlations using IBM SPSS Statistics v.28. Results. Results revealed a significant gap between coaches' high perceived importance of set pieces (M = 4.07 ± 0.98, Bulgarian; M = 4.10, international) and their relatively low ratings of current quality in Bulgarian football (M = 2.43 ± 0.81). Training frequency was predominantly once per week (42.5%), and multimodal communication methods were adopted by only 6.7% of Bulgarian coaches. Significant associations were found between coaching license and training frequency (χ² = 53.34, p < .001, V = .20), competition level and use of structured schemes (χ² = 63.07, p < .001, V = .31), and license level and analytical practices (χ² = 87.60, p < .001, V = .30). Strong Spearman correlations confirmed that higher qualification (rs = .89), elite competition level (rs = .92), and greater perceived goal contribution from set pieces (rs = .85) were all positively associated with deeper preparation investment. Conclusion. Findings indicate a systemic perception–practice gap and underscore the need for structured methodological support, visual communication tools, and specialized coaching roles. This study contributes by providing empirical evidence to support the development of structured methodologies, enhanced analytical integration, and specialized coaching roles in football training systems.